Identifying the Interunit Linkages Connecting Free Phenolic Terminal Units in Lignin. Issue 12 (13th May 2021) - Saito, Kaori; Makimura, Yutaka; Nishimura, Hiroshi; Watanabe, Takashi
Abstract: Understanding the linkages connecting phenolic terminal and nonphenolic units in complex branched polymer, lignin, is crucial to facilitate efficient and selective valorization of lignin. In this study, the interunit linkages connecting phenolic units are identified by premethylation of the phenolic hydroxy groups and thioacidolysis‐desulfuration. Interestingly, the phenolic units are found to be connected by only β‐5, β‐1, and β‐O‐4 linkages. The phenolic unit abundance is approximately 20 %. The result reveals that lignin polymerization terminates with the three linkages by a coupling between a monomer and the polymer terminus, which is reasonably explained by the radical coupling mechanism. Unexpectedly, 5‐5, 4‐O‐5, and β–β linkages connecting the phenolic units are not detected, indicating that these units are further elongated to form nonphenolic units. This study reveals the linkage types connecting phenolic and nonphenolic units and their elongation mechanisms. Abstract : Find the connection : Phenolic terminal units in a complex lignin polymer are identified by methylation labeling of the phenolic hydroxy groups and thioacidolysis. The results demonstrate various interunit linkages to be favorable or unfavorable for forming phenolic units, as well as the elongation mechanisms for phenolic and nonphenolic units. These findings contribute substantially to improving the efficiency of lignin depolymerization.